ANALISA STABILITAS MODEL KEMOSTAT UNTUK DUA MIKROORGANISME - , HERRI SULAIMAN ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Growth chamber in chemostat allows the interaction between the two microorganisms and can be modeled mathematically. Because of the rate of displacement and response functions in a mathematical model described it difficult to find exact solution in the system. However, things that can be done to addres those issues one of which is the behavior of the solution investigated by linearization around the equilibrium point. Futher it can be seen the stability of the system was investigated in two stages